La cosecha de maíz en Yucay - Mayta Medina, Faustino (1971)
The presentation of this work does not suppose a hypothesis that requires a doctrinal approach, scientifically essential. The compilation of the field material is due to the need to satisfy the question "How do traditional, magical-religious rites work in agricultural work and what are the socio-cultural consequences in the process of changes that are taking place in the valley? sacred to the Incas? The workers and some students of the Yucay Farm were the informants for this data collection, which, in our opinion, reflects reality without distorting it.